Objective understanding of the front-of-pack nutrition label Nutri-Score by European consumers. (30th September 2020) - Egnell, M; Talati, Z; Galan, P; Andreeva, V; Vandevijvere, S; Gombaud, M; Dréano-Trécant, L; Hercberg, S; Pettigrew, S; Julia, C
Abstract: Background: The effectiveness of Front-of-Pack nutrition Labels (FoPL) may be influenced by national context. In light of the ongoing efforts to harmonize nutrition labelling across Europe, the study aimed to compare the effectiveness of five FoPLs (Health Star Rating system [HSR], Multiple Traffic Lights [MTL], Nutri-Score, Reference Intakes [RIs], Warning symbol) in 12 European consumers. Methods: In 2018-2019, for three food categories, approximately 1, 000 participants per country were asked to select which food they would prefer to purchase between three products with distinct nutritional quality, and then to rank the products nutritional quality. Participants completed these tasks first with no FoPL and then, after randomization to one of the five FoPLs, with a FoPL on food packages. Associations between FoPLs and change in (i) nutritional quality of food choices, and (ii) ability to correctly rank the products nutritional quality were assessed with multivariable logistic regression models. Results: Compared with the RIs, the Nutri-Score (OR = 3·23[2·75-3·81]; p < 0.0001), followed by the MTL (OR = 1·68[1·42-1·98]; p < 0.0001), was the most effective FoPL in helping participants identify the foods nutritional quality, overall and in each of the 12 countries. Differences between FoPLs regarding food choice modifications were smaller, but the effect of the Nutri-Score was slightly higher in eliciting healthier food choices overall compared with the RIs, followed by the Warning symbol, MTL and HSR. Conclusions: These findings from an online experiment provide insights on the Nutri-Score's effectiveness in multiple European countries in the context of FoPL harmonization in Europe. Key messages: The comparison of the effectiveness of front-of-pack labels highlighted the relative performance of various types of labels, the Nutri-Score showing a higher performance than other schemes. The higher performance of the Nutri-Score was identified for objective understanding and to a lesser extent food choices.